2014
DOI: 10.18632/oncotarget.2007
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functionality of histone H2A variants in cancer

Abstract: Regulation of gene expression includes the replacement of canonical histones for non-allelic histone variants, as well as their multiple targeting by postranslational modifications. H2A variants are highly conserved between species suggesting they execute important functions that cannot be accomplished by canonical histones. Altered expression of many H2A variants is associated to cancer. MacroH2A variants are enriched in heterocromatic foci and are necessary for chromatin condensation. MacroH2A1.1 and macroH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 122 publications
(158 reference statements)
0
62
0
Order By: Relevance
“…Fifth, and quite interestingly, H2A.Z has been shown to redistribute to active gene bodies upon B-cell lymphomagenesis (Conerly et al, 2010). Given the established role of H2A.Z in cancer (Dryhurst and Ausio, 2014; Monteiro et al, 2014; Rangasamy, 2010), this raises the possibility that H2A.Z-mediated cryptic transcription may contribute to carcinogenesis. Also in favor of such a model, a recent study established that FACT acts as an “accelerator” of tumor formation (Garcia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, and quite interestingly, H2A.Z has been shown to redistribute to active gene bodies upon B-cell lymphomagenesis (Conerly et al, 2010). Given the established role of H2A.Z in cancer (Dryhurst and Ausio, 2014; Monteiro et al, 2014; Rangasamy, 2010), this raises the possibility that H2A.Z-mediated cryptic transcription may contribute to carcinogenesis. Also in favor of such a model, a recent study established that FACT acts as an “accelerator” of tumor formation (Garcia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Also in favor of such a model, a recent study established that FACT acts as an “accelerator” of tumor formation (Garcia et al, 2013). Since high H2A.Z levels have been associated with cancer progression and a negative prognosis (Dryhurst and Ausio, 2014; Monteiro et al, 2014; Rangasamy, 2010), and because aberrant transcription is a well-recognized hallmark of cancer, activation of cryptic transcription by H2A.Z represents a new model for pathological changes to gene expression that merits scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…11,17,22 Additionally, deregulation in macroH2A.1 alternative splicing has been related to the metastatic transition in several types of cancer. [23][24][25] Several in vivo and in vitro studies indicate that macroH2A increases nucleosome stability due to the specific structural features of its H2A domain. 26,27 It has also been shown that the structural changes resulting from the incorporation of macroH2A into nucleosomes prevent the access to chromatin by some remodeling complexes (e.g., SWI/SNF).…”
Section: Introductionmentioning
confidence: 99%
“…Histone variants mediate a variety of functions, such as modifying expression, controlling chromatin condensation, sensing DNA damage, and controlling the cellular response toward DNA damage repair or apoptosis [186]. MacroH2A isoforms are unique H2A histone variants due to the presence of a 30-kDa non-histone domain (macro domain) at their C-termini.…”
Section: Deregulation Of Ecsod In Cancersmentioning
confidence: 99%